Proceedings of the 15th ACM Asia Conference on Computer and Communications Security 2020
DOI: 10.1145/3320269.3384730
|View full text |Cite
|
Sign up to set email alerts
|

I came, I saw, I hacked: Automated Generation of Process-independent Attacks for Industrial Control Systems

Abstract: Malicious manipulations on Industrial Control Systems (ICSs) endanger critical infrastructures, causing unprecedented losses. Stateof-the-art research in the discovery and exploitation of vulnerability typically assumes full visibility and control of the industrial process, which in real-world scenarios is unrealistic. In this work, we investigate the possibility of an automated end-to-end attack for an unknown control process in the constrained scenario of infecting just one industrial computer. We create dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…These attacks impact the various critical processes of the plant by manipulating the controller and sensor data. Sarkar et al, 51 studied the impact of control‐theoretic attacks on the operational capabilities of the power plant. These attacks are different from the other attacks, as the designing of these attacks requires deep analysis of the sector on which it has to be launched.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These attacks impact the various critical processes of the plant by manipulating the controller and sensor data. Sarkar et al, 51 studied the impact of control‐theoretic attacks on the operational capabilities of the power plant. These attacks are different from the other attacks, as the designing of these attacks requires deep analysis of the sector on which it has to be launched.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, it has been observed that these attacks are targeted on sensors or actuators. 47 Sarkar et al, 51 mentioned that these attacks cause a deviation or perturbation in the physical quantity. These deviations can be of two types: stable and oscillatory.…”
Section: Control-theoretic Attacksmentioning
confidence: 99%
“…Attacking sensors means varying the water level in the tank. The authors in [ 50 , 51 ] studied an experimental setup to explain the disturbance in the water level in an ICS environment while attacking through actuators to vary the data linked pumping speed and implement a DoS attack. Attacking via the communication link between sensors and PLC means varying the PLC-collected data and getting water status information; attacking via the actuators and PLC communication link means changing the signals and sending wrong information.…”
Section: Attack and Defense Modelmentioning
confidence: 99%
“…Attackers with access to HMIs have a larger view of the system than individual PLCs. Attackers with access to HMIs could infer a more general view of the system, such as the type of industry they control [28].…”
Section: Process Knowledge Data Sourcesmentioning
confidence: 99%
“…Due to the large number of attacks required to obtain the ground-truth, we opted for a simulated environment where the attacks can be executed without safety concerns. The simulated plant is known as the Tennessee Eastman Plant and has been extensively used in previous cybersecurity research [7,13,15,16,28].…”
Section: Experimental Evaluationmentioning
confidence: 99%